Comprehensive Structural Descriptor for Electrocatalytic Oxygen Evolution Activities of Iron Oxides. Issue 23 (15th October 2021) - Sugawara, Yuuki; Kamata, Keigo; Hayashi, Eri; Itoh, Mitsuru; Hamasaki, Yosuke; Yamaguchi, Takeo
Abstract: To determine the structural descriptor of the oxygen evolution reaction (OER) in a wide range of Fe‐based oxides, we investigate Fe2 O3 polymorphs. Remarkably, the OER activity of the polymorphs strongly depends on the atomic configurations in the crystals, and shorter Fe−O bond lengths are more beneficial for the OER. DFT calculations reveal that the trend of Fe−O bond length on the Fe2 O3 polymorphs exhibits a positive correlation with their energy gaps between the occupied oxygen 2p and the unoccupied iron 3d orbitals, i. e., charge‐transfer energy, which promotes the OER activities of metal oxides. Surprisingly, the relationship between the Fe−O bond length and the OER activity can also be applied to a wide range of previously reported Fe‐based multimetal oxide OER catalysts, regardless of their chemical compositions and categories of crystal structures, including perovskite, spinel, brownmillerite, and other types of oxides. The discovered descriptor is an important guideline for the rational design of Fe‐based oxides with excellent catalytic properties for the OER and contributes to the establishment of a hydrogen society. Abstract : Four types of Fe2 O3 polymorphs are investigated to unveil the comprehensive descriptor for electrocatalytic oxygen evolution reaction (OER) in Fe‐based oxides. Shorter Fe−O bond lengths in the catalyst crystals are reportedly more beneficial for the OER. Remarkably, this descriptor can also be applied to a wide range of Fe‐based multimetal oxides regardless of their chemical compositions and crystal structures.